Regenerative potential of graphene oxide-chitosan nanocomposite combined with fetal bovine serum on healing of full-thickness skin wound in rats - Kamal H. Hussein; Mahmoud Soliman; Mahmoud S. Sabra; Hani Nasser Abdelhamid; Mahmoud Abd-Elkareem; Ahmed Abdelrahiem Sadek (BMC Veterinary Research)
Abstract Background Delayed wound closure and non-healing wounds represent a problematic condition with health burden and an economic challenge. Therefore, different strategies have been developed, including skin tissue engineering, which aims to stimulate and support the wound healing process. In this study, the potential of graphene oxide (GO) and chitosan (CTS) biomaterial composite, with and without fetal bovine serum (FBS), was investigated to induce a full-thickness skin wound repair in rats. Methods The GO-CTS composite was characterized using X-ray diffraction, transmission electron microscopy, and Fourier transforms infrared. Cytocompatibility was evaluated via an MTT assay with human endothelial cells (ECs) and mouse embryonic fibroblasts (MEFs) in vitro. The in vivo wound regeneration potential was assessed by creating an 8 mm full-thickness circular skin defect on the dorsal surface of the rat. The defects were randomly divided into control, GO-CTS, FBS, and GO-CTS/FBS groups, and were monitored grossly and histologically at days 7 and 21 after wound induction. Results The GO-CTS material demonstrated high cytocompatibility, with cell viability recorded at 99.2% ± 5.7% for ECs and 110.5% ± 3.9% for MEFs. The highest proliferation rates were observed in the FBS (118.2% ± 2.1%) and GO-CTS/FBS (121.4% ± 4.4%) groups. In vivo, wound closure rates on day 21 were 85.5% ± 0.56% for GO-CTS, 87.5% ± 1.75% for FBS, and 91.5% ± 1.03% for GO-CTS/FBS, all significantly higher than the control group. Additionally, neovascularization, epithelialization, collagen deposition, and granulation tissue formation were more prominent in the treated groups, with skin appendages observed in the GO-CTS/FBS group. Conclusion GO-CTS nanosheets with FBS represent a promising biomaterial for skin tissue engineering and can effectively initiate and support wound healing.